LEED structure determination of the (100)-surface of a CoSi2 crystal and a CoSi2 film grown epitaxially on Si(100) - Weiss, Wolfgang; Starke, Ulrich; Heinz, Klaus; Rangelov, Georgi; Fauster, Thomas; et al. (Surface Science, 1996)
The surface structures of CoSi2(100) for a bulk crystal and a 12 Angstrom thin film grown epitaxially on Si(100) are compared by means of quantitative low energy electron diffraction (LEED). Similar LEED patterns are observed for both systems corresponding to a c(2 x 2) periodicity with respect to the Si(100) surface. Also, intensity versus energy curves are very similar for the film and bulk samples. Consequently, we derive practically the same best-fit model when fitting the experimental data with spectra obtained from full dynamical LEED calculations: the CoSi2 surface is arranged in CaF2 structure, terminated by one full Si layer with an additional c(2 x 2) Si overlayer of half monolayer coverage. The top silicon adatoms reside in four-fold symmetric hollow sites. The unfavourable energetics of this rather peculiar bonding geometry are obviously overcompensated by the energy gain from the saturation of dangling bonds on the surface. The geometry found is consistent with the chemical passivity of the surface.
Keywords: cobalt; epitaxy; low-energy electron diffraction (LEED); low index single crystal surfaces; silicides; silicon; surface relaxation and reconstruction; surface structure